2014
DOI: 10.9775/kvfd.2013.9601
|View full text |Cite
|
Sign up to set email alerts
|

Laminektomi Yapılan Tavşanlarda Alfa-lipoik Asit Uygulamalarının Total Antioksidan Kapasite, Total Oksidan Kapasite, Paraoksonaz ve Total Sialik Asit Düzeyleri Üzerine Etkilerinin Araştırılması

Abstract: The objective of this study is to investigate the effect of intramuscular administration of alpha-lipoic acid (ALA) on total antioxidant (TAS), total oxidant (TOS), paraoxonase (PON) and total sialic acid (TSA) levels in laminectomized rabbits. In the study, twenty four white New Zeeland rabbits weighing 3-4 kg were used. The investigation was carried out with three experiment and one control group consisting of six animals of each. No intervention has been done to the control group. Animals in the Group I rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Yıldırım et al investigated the effect of intramuscular alpha-lipoic acid administration on TAC and TOS levels in laminectomized rabbits. 20 It has been suggested that laminectomy causes changes in total sialic acid, and total antioxidant status (TAS) levels; on the other hand, supported plasma antioxidant capacity by increasing TAS and decreasing TOS levels in animals. BPA has dosedependent deleterious effects, and increased amounts of TOS have been detected, as seen after laminectomy surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yıldırım et al investigated the effect of intramuscular alpha-lipoic acid administration on TAC and TOS levels in laminectomized rabbits. 20 It has been suggested that laminectomy causes changes in total sialic acid, and total antioxidant status (TAS) levels; on the other hand, supported plasma antioxidant capacity by increasing TAS and decreasing TOS levels in animals. BPA has dosedependent deleterious effects, and increased amounts of TOS have been detected, as seen after laminectomy surgery.…”
Section: Discussionmentioning
confidence: 99%